Assessment of the mass casualty triage during the November 2015 Paris area terrorist attacks: towards a simple triage rule. (27th November 2020) - James, Arthur; Yordanov, Youri; Ausset, Sylvain; Langlois, Matthieu; Tourtier, Jean-Pierre; Carli, Pierre; Riou, Bruno; Raux, Mathieu
Abstract : Supplemental Digital Content is available in the text. Abstract : Backround: Triage is key in the management of mass casualty incidents. Objective: The objective of this study was to assess the prehospital triage performed during the 2015 Paris area terrorist attack. Design setting and participant: This was a retrospective cohort study that included all casualties of the attacks on 13 November 2015 in Paris area, France, that were admitted alive at the hospital within the first 24 h after the events. Patients were triaged as absolute emergency or relative emergency by a prehospital physician or nurse. This triage was then compared to the one of an expert panel that had retrospectively access to all prehospital and hospital files. Outcomes measures and analysis: The primary endpoints were the rate of overtriage and undertriage, defined as number of patients misclassified in one triage category, divided by the total number of patients in this triage category. Main result: Among 337 casualties admitted to the hospital, 262 (78%) were triaged during prehospital care, with, respectively, 74 (28%) and 188 (72%) as absolute and relative emergencies. Among these casualties, the expert panel classified 96 (37%) patients as absolute emergencies and 166 (63%) as relative emergency. The rate of undertriage and overtriage was 36% [95% confidence interval (CI), 27–47%] and 8% (95% CI, 4–13%), respectively. Among undertriaged casualties, 8 (23%) were considered as being severely undertriaged. Among overtriaged casualties, 10 (77%) were considered as being severely overtriaged. Conclusion: A simple prehospital triage for trauma casualties during the 13 November terrorist attack in Paris could have been performed triaged in 78% of casualties that were admitted to the hospital, with a 36% rate of undertriage and 8% of overtriage. Qualitative analysis of undertriage and overtriage indicate some possibilities for further improvement.